Evaluation of the new technologies in order to facilitate democracy in Europe - Trechsel, Alexander; Kies, Raphael; Mendez, Fernando; Schmitter, Philippe; Triga, Vasiliki; Vulliez, Valérie (My University, 2003)
This report is about the one of the latest changes in the ‘technology of democracy’and how it may impact on some of our core institutions of democratic representation: parliaments and parties. As in the past, whenever something new was injected into the processes of election and representation pundits have emerged to argue that the nature of democracy would be transformed. This is no less true for one of the latest potential changes in the ‘technology of democracy’, namely the introduction into the democratic realm of information and communication technologies (ICT). This report evaluates whether the introduction and diffusion of ICT is having a significant impact upon the practice of democracy in the member and candidate states of the European Union. Two research strategies have been employed: The first is a comparative website analysis of parliamentary and political parties’ websites. The second is a series of case studies and country reports which focus on edemocracy initiatives across the 26 polities we survey. The results of our core empirical analysis indicate that there is considerable variation among both parliaments and parties as far as the development of their websites is concerned. Existing member states tend to have more developed websites and, overall, the quality of parliamentary websites tends to be slightly superior to that of party websites. Most surprisingly, familiarity and use of ICT–as well as higher levels of wealth-do not inexorably lead to better website development. Differences in party systems–its fragmentation, ideological orientation, levels of turnout, distribution of major and minor parties-also do not seem to have a …